Photocatalytic hydrogen production under visible light over Cd0.1SnxZn0.9-2xS solid solution photocatalysts - Melody, Kimi; Leny, Yuliati; Mustaffa, Shamsuddin (Elsevier Ltd., 2011)
A series of Cd0.1SnxZn0.9-2xS solid solution was successfully synthesized by hydrothermal method and employed as photocatalyst for photocatalytic hydrogen evolution under visible light irradiation. The structures, optical properties and morphologies of the solid solutions were studied by X-ray diffraction, diffuse reflectance UVevisible spectroscopy and field emission scanning electron microscopy. From the characterizations, it was confirmed that Sn can form solid solution with Cd0.1Zn0.9S and the high crystallinity can be maintained as well. Among all samples, the highest photocatalytic activity was observed on Cd0.1Sn0.01Zn0.88S photocatalyst, with average rate of hydrogen production 3.52 mmol/h, which was ca. 1.5 times higher than the Cd0.1Zn0.9S photocatalyst. In addition to the high activity, the Cd0.1Sn0.01Zn0.88S also showed high stability at long irradiation time. The role of Sn in preventing electron-hole recombination and photocorrosion was proposed.